MINDflex Training for Cognitive Flexibility in Chronic Pain: A Randomized, Controlled Cross-Over Trial - Jacobsen, Henrik B.; Klungsøyr, Ole; Landrø, Nils I.; Stiles, Tore C.; Roche, Bryan T. (Frontiers in Psychology, 2020)
Abstract: Impairments in executive functioning are prevalent in chronic pain conditions, with cognitive inflexibility being the most frequently reported. The current randomized, cross-over trial, piloted a computerized cognitive training (CCT) program based on Relational Frame Theory, targeting improvement in cognitive flexibility. At baseline, seventy-three chronic pain patients completed testing on pre-selected outcomes of executive functioning, alongside IQ measures. When tested three times over the course of five months, there was a drop-out rate of 40 % at the third time point, leaving 44 patients who had data at all time points. The results showed that there was a substantial learning effect from the MINDFLEX training and a substantial time-dependent improvement on the primary outcomes of increased flexibility, but that this could not be tied to active training. In conclusion, this small study indicated a learning effect as well as improvement on primary outcomes. Based on the current results, a larger trial with improved feasibility of training is warranted.